Mapping Grammatical Relations of English Verbs - Arta, Putu Owen Purusa; Sedeng, I Nyoman; Soethama, Putu Lirishati (Humanis, 2022)
This study entitled Mapping Grammatical Relations of English Verbs, concerns on numbers of arguments that a verb could assign and how an argument is syntactically motivated in clauses of which the mood is declarative. This study involves to library research , and the method that was applied in this study was descriptive method which describes linguistics phenomena like what it actually is. The data of this study were taken from the Corpus of Contemporary American English (COCA) by inputting verbs those have been determined to the website http://www.english-corpora.org/coca/. The main theory applied in this study was Kroeger’s (2005) regarding to transitivity and grammatical relation. Based on the analysis, verbs in English require argument(s), terms or obliques. An intransitive verb assigns a term that stands as subject, a transitive verb assigns two terms those stand as subject and primary object. On the other hand, a ditransitive verb assigns three terms those stand as subject, primary object and secondary object. In addition, there is an argument that stands as oblique.